Strengthening School Counseling Guidance Activities through e-counseling - Harsani, Prihastuti; Erniyati, Erniyati; Kurnia, Dadang (Research Collaboration Community (Rescollacom), 2022)
Cybercounseling is defined as a professional counseling practice that occurs when the counselee and counselor are separately and utilize electronic media to communicate via the internet. Several problems arise in student coaching activities by Guidance Counseling teachers, namely: not yet optimal use of cyber counseling applications, recording of student progress, which is still done manually, and the unavailability of facilities for students to express academic and non-academic problems. The technology provided is an e-counseling application. The method used in this activity is an e-counseling implementation workshop. Computer Vocational Schools as partners have been involved in the stages of needs identification, implementation, and trials. The school elements involved are Principals, Students, BK teachers, and homeroom teachers. This technology provides an alternative repository of student development. Based on the results of the workshop, it was found that the repository was available at 85% and the usability level of the system was 75%.